Lapatinib as a Dual Tyrosine Kinase Inhibitor Unexpectedly Activates Akt in MDA-MB-231 Triple-Negative Breast Cancer Cells - Kaboli, Parham J.; Ling, King-Hwa (Letters in Drug Design & Discovery, 2020)
Background: MDA-MB-231 is a Triple-Negative Breast Cancer (TNBC) cell line, which is resistant to tyrosine kinase inhibitors, such as lapatinib. Lapatinib is well-recognized as an anti- EGFR and anti-Her2 compound. Here, we report one of the possible explanations for lapatinibresistance in TNBC cells, the most incurable type of breast cancer. Methods: Using western blotting, we have observed that lapatinib-treated cells enhanced activation of Akt, an oncogenic protein activated at downstream of EGFR signaling. Results: Anti-EGFR activity of Lapatinib would be counteracted with sustained activation of Akt. We found lapatinib-resistance in TNBC can be managed by administering Akt inhibitors. Further, lapatinib enhanced PI3K/Akt signaling is an alternative pathway to ensure the viability of MDAMB- 231 cells. There might also be unknown targets for lapatinib, which needs further investigation. Conclusion: This observation opens up a new discussion on overcoming resistance to tyrosine kinase inhibitors, a key challenge in treating TNBC.
Keywords: EGFR